Investigation of Staff's Job Satisfaction and Related Factors in TUMS Teaching Hospital - Seyed Mohammad Hadi Mousavi; Hossein Dargahi; Mojgan Asgari; Roya Sharifiyan; Golsa Shaham; Zahra Mokhtari (Tehran University of Medical Sciences, 2016)
Background and Aim: Organizational productivity and efficiency depends on staff members' job satisfaction and performance. Without the participation of staff members, hospitals cannot play an important role in promoting the society's health. This study aimed to determine staff's job satisfaction in a teaching hospital of Tehran university of Medical Sciences (TUMS). Materials and Methods: This descriptive, analytical cross-sectional research was conducted on 172 staff members of a teaching hospital, who had been selected through random sampling. The data-collection tool was a researcher-made questionnaire. The validity of the questionnaire was confirmed by the clinical governance department members and Cronbach's alpha reliability estimate turned out to be 0.88.  Results: Para-clinical and service employees getting the mean scores of 72.55 and 70.71 demonstrated desired job satisfaction; nursing and administrative-financial staff members, however, showed a relatively desired job satisfaction with mean scores of 60.04 and 53.52, respectively; and the difference between job groups was significant (p=0.02) regarding job satisfaction. The highest job satisfaction figure was related to job success and the lowest pertained to the nature of the job. There was a meaningful relationship between job satisfaction on the one hand and staff members' gender, marital status, and type of employment on the other. Conclusion: Staff's job satisfaction in the studied hospital has increased due to the establishment of Iran's Healthcare Reform Plan at the beginning of 2014. However, compared with other job groups, nurses are less satisfied; therefore, it is necessary to improve nursing job satisfaction through timely payments based on job performance and difficulty level.